The Dividing Power of the Wage: Housework as Social Subversion - Rousseau, Christina (Atlantis)

(untitled) (Mount Saint Vincent University, 2016)
In this article, I revisit the Wages for Housework (WfH) perspective and movement in order to recover Marxist-feminist analyses of social reproduction. Social reproduction remains an important site of contestation, especially as women continue to bear the brunt of an increasingly neo-liberalized economy. WfH’s nuanced view of wages and housework, I argue, should be reconsidered as a point of departure in responding to new forms of oppression in a re-organized economy.